Ein Fair New Deal für Deutschland - Tom Krebs; Isabella M. Weber (Wirtschaftsdienst, 2025)
– We propose a Fair New Deal for Germany. First, the German government needs to implement a public investment package that puts the German economy on a prolonged growth path. The main mechanisms of this first component of the Fair New Deal are electricity price controls, expansion of public infrastructure investment, subsidies to green private investments, and an increase in the public demand for green products. Second, policies have to be established to ensure that as many people as possible gain from economic growth. To this end, the German government has to modify the Minimum Wage Law, condition investment subsidies and public goods purchases on wages, and provide more child care and full-day schooling. We also discuss how to finance the necessary increase in public spending within the constraints of the German debt brake.
Keywords: E60; L50; J50; 330; Wirtschaftspolitik; Deutschland; Wirtschaftspolitik; Deutschland